2017
DOI: 10.1136/bmj.j1797
|View full text |Cite
|
Sign up to set email alerts
|

Physician age and outcomes in elderly patients in hospital in the US: observational study

Abstract: Objectives To investigate whether outcomes of patients who were admitted to hospital differ between those treated by younger and older physicians. Design Observational study. Setting US acute care hospitals. Participants 20% random sample of Medicare fee-for-service beneficiaries aged ≥65 admitted to hospital with a medical condition in 2011-14 and treated by hospitalist physicians to whom they were assigned based on scheduled work shifts. To assess the generalizability of findings, analyses also included pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 40 publications
4
127
3
4
Order By: Relevance
“…Our results showed that older attending physicians (>50 years) were associated with failure. Tsugawa et al 29 investigated the association between 30-day mortality rates and healthcare costs in acute care hospitals, and found that mortality rates were higher among older physicians, which is similar to our results. We did not assess the length of time spent explaining the eradication therapy and the drug [32][33][34] It has also been shown that younger age is a risk factor for unsuccessful clinical outcomes among HIV patients.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that older attending physicians (>50 years) were associated with failure. Tsugawa et al 29 investigated the association between 30-day mortality rates and healthcare costs in acute care hospitals, and found that mortality rates were higher among older physicians, which is similar to our results. We did not assess the length of time spent explaining the eradication therapy and the drug [32][33][34] It has also been shown that younger age is a risk factor for unsuccessful clinical outcomes among HIV patients.…”
Section: Discussionsupporting
confidence: 90%
“…One of the most important findings of this study is that younger oncologists were more likely to refer patients to palliative care. Our findings are consistent with recent literature suggesting that patients of younger physicians may have better outcomes . We hypothesize that younger oncologists were (a) more familiar with the concept of early palliative care compared with their more senior colleagues, (b) more prepared to adopt new advances based on the literature, and (c) more willing to adhere to clinical practice guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…More information on these variables and their sources has been detailed elsewhere. 19,3336 Finally, using Medicare claims, we estimated Medicare fee-for-service panel size via the attribution methods detailed above (prior to exclusion of any patients or physicians from the sample), adjusting panel sizes to account for the 20% random sampling.…”
Section: Methodsmentioning
confidence: 99%